Persistent infectious diseases say – IDO. Role of indoleamine-2, 3-dioxygenase in disease pathogenesis and implications for therapy. (November 2014) - Barth, Heidi; Raghuraman, Sukanya
Abstract Indoleamine-2, 3-dioxygenase (IDO) is an enzyme that catabolises tryptophan – an essential amino acid critical for T cell proliferation. Initially recognized as a first line of host defense against infectious pathogens, IDO has been subsequently identified as an important immune-regulator inhibiting T-cell responses and promoting immune tolerance. Research over the past few years has demonstrated a crucial role for IDO in the pathogenesis of persistent infections that place an enormous burden on public health. In this review, we summarize current knowledge about IDO's role in causing pathogen persistence and progression to clinical disease. We conclude with a perspective on the potential benefits and risks of therapeutic IDO manipulation.